The role of reliability and tangibility in increasing the competitiveness of commercial banks in Algeria - Case study at commercial banks in Algeria - houssameddine, abdelhafid (Université de M'sila, 2020)
The aim of this study is to emphasize the important role of the reliability and tangibility dimension, which are considered to be one of the most important dimensions of the quality of the banking service in terms of impact and increase of competitiveness in Algerian commercial banks, by caring for the customer who is the most important and dynamic element in commercial banks, We tested reliability and tangibility by doing two hypothesis tests based on a questionnaire that was answered by 128 customers in several banks located in Algeria. Finally, we found that reliability, tangibility has a positive impact on the competitiveness of Algerian commercial banks. Keywords: Reliability ; Tangibility ; Customers ; Competitiveness